The effect of plyometric training on some motoric and technical parameters in 13-15 age soccer players - Caliskan, Ö.; Arikan, S. (Turkish Journal of Sport and Exercise, 2021)
The aim of this study was to examine the effect of regular plyometric training on some motoric and technical parameters of young soccer players in addition to regular soccer training. A total of 25 male volunteers (13 training group, 12 control group) aged between 13-15 studying at Konyaspor Infrastructure Soccer School participated in the study. The training group followed an 8-weeks, 2 days a week and 30 minutes plyometric training program in addition to the regular soccer training. The control group players continued their normal soccer training. In order to determine some motoric and technical characteristics of the players body weight of all participants were recorded before and after the study. Also vertical jump, standing long jump, T agility test, 20 meter sprint, speed dripling test, and Mor-Christian shot ability test measurements were taken. SPSS 22.0 IBM statistical package program was used to evaluate the data obtained within the scope of the research. In order to determine the difference between the groups, t test was used in independent groups and paired sample t test was used to compare the pre-test and post-test values. According to the research findings when the pre-test and post-test values of the training and control groups were compared, only a significant difference was observed in the dribbling values at the beginning of the study, but at the end of 8 weeks there was a statistically significant difference in agility, shot and dribbling values in favor of the training group (p <0.05). In addition, it was found that there was a statistically significant difference between the pre-test and post-test values of all the parameters of the players who participated in the training group (p <0.05), but there was no statistically significant difference in the control group (p> 0.05). As a result, it can be said that plyometric exercise applied in addition to regular soccer training has positive effect on some motoric and technical characteristics of 13-15 age soccer players.